The Effect of Teachers’ Beliefs on Second Language Writing Practice: Case Studies in a Saudi University - Alkubaidi, Miriam (Advances in Social Sciences Research Journal, 2022)
This study attempts to fill in a gap found in the literature regarding the Saudi higher education context in terms of the second language (L2) teachers’ perception on second language writing (SLW), and their practice in their classrooms. A case study was employed to explore the beliefs and practices of four female EFL teachers in association to second language writing practices. First semi-structured interviews were conducted whereby the beliefs of the teachers’ writing practice. A series of questions related to the teachers writing classes specifically and teaching writing as a whole in the centre. This study has focused on the teachers’ own personal beliefs on how teaching SLW should take place by looking back at their background, educational vision, and the methods/approaches used/thought in the classroom. The study has explored the teachers’ practice of SLW in the classroom and compared them to their teachers’ beliefs of SLW.